Calculați complet A+B și A-B, știind că:
![Calculați Complet AB Și AB Știind Că class=](https://ro-static.z-dn.net/files/dce/531c6308d77dbe40dd326c5b91016037.jpg)
Explicație pas cu pas:
a ) A = 16√3 - 18√3 + 19√3 - 15√3 - 12√3 + 20√3
A = √3( 16 - 18 + 19 - 15 - 12 + 20 )
A = √3( -2 + 19 - 15 - 12 + 20 )
A = √3( 17 - 15 - 12 + 20 )
A = √3( 2 - 12 + 20 )
A = √3( -10 + 20 )
A = √3 x 10
A = 10√3
B = 10√3 - 12√3 - 14√3 + 18√3 - 16√3 + 13√3
B = √3(10 - 12 - 14 + 18 - 16 + 13 )
B = √3(-2 - 14 + 18 - 16 + 13 )
B = √3(-16 + 18 - 16 + 13 )
B = √3(2 - 16 + 13 )
B = √3(-14 + 13 )
B = √3 x ( -1 )
B = -√3
A + B = 10√3 + ( -√3 )
A + B = 9√3
A - B = 10√3 - ( -√3 )
A - B = 11√3
-------------------------------------------------
b ) A = 17√5 - 19√5 - 14√5 + 11√5 - 16√5 + 12√5
A = √5(17 - 19 - 14 + 11 - 16 + 12 )
A = √5(-2 - 14 + 11 - 16 + 12 )
A = √5(-16 + 11 - 16 + 12 )
A = √5(-5 - 16 + 12 )
A = √5(-21 + 12 )
A = √5 x ( -9 )
A = -9√5
B = 12√5 - 9√5 + 7√5 - 14√5 + 16√5 - 13√5
B = √5(12 - 9 + 7 - 14 + 16 - 13 )
B = √5(3 + 7 - 14 + 16 - 13 )
B = √5(10 - 14 + 16 - 13 )
B = √5(-4 + 16 - 13 )
B = √5(12 - 13 )
B = √5 x ( -1 )
B = -√5
A + B = -9√5 + ( -√5 )
A + B = -10√5
A - B = -9√5 - ( -√5 )
A - B = -8√5
------------------------------------------
c ) A = 6√3 + 17√3 - 21√3 - 14√3 + 15√3 - 10√3
A = √3(6 + 17 - 21 - 14 + 15 - 10 )
A = √3(23 - 21 - 14 + 15 - 10 )
A = √3(2 - 14 + 15 - 10 )
A = √3(-12 + 15 - 10 )
A = √3(3 - 10 )
A = √3 x ( -7 )
A = -7√3
B = 9√3 - 21√3 + 15√3 - 14√3 + 18√3 - 12√3
B = √3(9 - 21 + 15 - 14 + 18 - 12 )
B = √3(-12 + 15 - 14 + 18 - 12 )
B = √3(3 - 14 + 18 - 12 )
B = √3(-11 + 18 - 12 )
B = √3(7 - 12 )
B = √3 x ( -5 )
B = -5√3
A + B = -7√3 + ( -5√3 )
A + B = -12√3
A - B = -7√3 - ( -5√3 )
A - B = -2√3